Validation and Reliability of Self-Efficacy English Learning of Health Vocational Students with Jigsaw Learning Strategy - Istanto, Wisnu; Amelia, Noer; Anggoro, Sapto Dwi (CV. Creative Tugu Pena, 2023)
The purpose of this study was to put to the test a self-efficacy survey of four language skills (listening, speaking, writing, and reading) using the Jigsaw Learning Strategy. This study was a descriptive qualitative study in which 20 question items about self-efficacy and four language skills in English mastery for health vocational students are tested. This qualitative study was carried out in two classrooms with 39 health vocational students each from January 2021 to August 2022. Two classrooms were set up for the lecture group, one for Jigsaw and one for non-Jigsaw. Self-efficacy questionnaires were used to gather information. In the learning group, there were fourteen sessions totaling two hours, during which each class learned the same practice and comprehension material. Four language skills were worked on by the students. The questionnaire data was analyzed by the product moment to determine validity, and all were found to be valid with results greater than the value of the r table and less than 0.025. The reliability test results on questionnaire data revealed that the data were reliable or consistent. The Keiser-Meyers-Oklin Self-Efficacy Measure in the group of questions for all questionnaire items could be considered appropriate. The Measure of Sampling Adequacy results were also used to determine whether the self-efficacy variable was large enough for further analysis. The communality value was greater than 0.03, indicating a positive relationship between variables. Descriptive analysis, jigsaw classes respond better to self-efficacy surveys than non-jigsaw classes, implying increased self-confidence in the English learning process. Keywords: Jigsaw Learning Strategy, Self-Efficacy English Learning, Validation and Reliability